Effect of PWHT Conditions on Toughness and Creep Rupture Strength in Modified 9Cr-1Mo Steel Welds - Nishikawa Satoru; Hasegawa Tadayuki; Takahashi Makoto (High Temperature Materials and Processes, 2019)
We clarified the effect of post weld heat treatment (PWHT) conditions on the toughness and creep rupture strength of modified 9Cr–1Mo steel weldments used for high temperature components of ultra-supercritical power plants. Fracture appearance transition temperature (FATT) decreased as PWHT temperature increased, and for all of the weld metals of tungsten inert gas welding, submerged arc welding and shielded metal arc welding, FATTs were lower than 293 K when the PWHT temperature was higher than 1,008 K. In contrast, in the uniaxial creep test with a loaded stress of 108 MPa, the creep rupture strength of the specimen on which PWHT was carried out for a holding time of 7.2 ks was significantly decreased when the PWHT temperature was more than 1,033 K. Therefore, the appropriate PWHT temperature range to maintain the toughness and creep fracture strength was 1,008 K ≤ T ≤ 1,033 K.